EDUKASI MENGENAI RASISME DAN KEBERAGAMAN MELALUI PODCAST - Raja Andiani Sebriwahyuni; Amalia Putri Yulandi; Elviana Elviana; Erlyna Juany; Jhon Indexon; Julianti Cesilia; Melvin Angtony; Venorika Venorika; Vera Vera (National Conference for Community Service Project (NaCosPro), 2020)
Since we born until now, of course, we live in an environment full of diversity such as culture, ethics, and many more. Sometimes with this diversity, it can make people unable to relate well and can’t live in harmony. But sometimes with this diversity, we can learn more about other people's opinions, cultures, or ethics. Whether people can deal with the difference or not, it all depends on their own selves, depending on what mindset did they think about. So, to prevent the bad mindset about diversity, we choose a program to educate and persuade people to respect each other and stay positive the difference by making a podcast. The podcast will be uploading to Spotify so that it will be easier to access or to listen.